PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVENING - Sofia, Euis Nurus; Akhmadi, Akhmadi (Faculty of Economics and Business - Universitas Sultasn Ageng Tirtayasa, 2018)
The purpose of this study was to determine whether there is influence between profitability and firm size on firm value, using debt policy as an intervening variable. This type of research is descriptive and associative. The population consumption listed company on the Stock Exchange in 2011-2015 by 41 companies using purposive sampling method obtained a sample of 21 companies. The data used is secondary data. Analysis of the data using the classical assumption test , partial test (t-test) and path analysis. By using SPSS (Statistik Product and Service Solution) 23 for windows. From the calculation, all the classical assumption has been fulfilled. The first regression equation namely, [X3 = 0,130 X1 + 0,166 X2 + 0,978]and a second regression equation namely,[Y = 0,474 X1+ 0,401 X2+ 0,213 X3+ 0,744]. The result of research partially profitability has positive effect and significant to firm value. Firm size has positive effect and significant to firm value. Debt policy has positive effect and significant to firm value. profitability has insignificant positive effect to debt policy. Firm size has insignificant positive effect to debt policy. Path analysis of the test results showed that the debt policy as an intervening variable is unable to mediate the effect of profitability on firm value and it’s influence is not significant. Debt policy as an intervening variable is also not able to mediate the effect of firm size on firm value and it’s influence is not significant.